K-State Turfgrass Research 2014 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2014)
Turfgrass Research 2014 contains results of projects conducted by K-State faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day on August 7, 2014, at the Rocky Ford Turf Research Center in Manhattan. Articles included in this Report of Progress present summaries of research projects that were completed recently or will be completed in the next year or two. Notice that each article is now presented as an individual file. This allows you to go directly to articles you have interest in and allows us to link the articles in other media outlets we use, such as Twitter and weekly blogs.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1107; Kansas Agricultural Experiment Station contribution; no. 14-xxx-S; Drought; Water management; Pest management; Kansas; Turfgrass